Chloroquine inhibits artificial oocyte activation induced by ethanol or Sr2+ but not by sperm in mice - Tadashi YAMAZAKI; Md Wasim BARI; Satoshi KISHIGAMI (The Journal of Reproduction and Development)
Calcium release from the endoplasmic reticulum via sperm-derived phospholipase C zeta is crucial for oocyte activation during fertilization. Chloroquine (CQ) inhibits the increase in cytoplasmic calcium. This study investigated the effects of CQ on fertilization and oocyte activation. Oocytes were collected from ICR mice, and in vitro fertilization and artificial oocyte activation with strontium ions (Sr2+) and ethanol were performed in the presence of 50 µM CQ. Pronuclear formation was assessed via Hoechst33242 nuclear staining, cortical granule release was evaluated using lens culinaris agglutinin-fluorescein isothiocyanate staining, and cytosolic calcium levels were measured using fluorescence microscopy with Cal-520 AM. In the presence of CQ, no pronuclei were formed even 8 h after Sr2+-induced oocyte activation. Furthermore, cortical granule release in CQ-treated oocytes was significantly suppressed, although not completely inhibited, and no increase in cytosolic calcium was detected. CQ also inhibited pronuclear formation during ethanol-induced oocyte activation. In in vitro fertilization, although the fertilization rate was decreased in the CQ-treated group, in which CQ treatment was continuously applied during insemination, pronuclear formation and cortical granule release were observed. The decrease in the fertilization rate was likely attributable to reduced sperm motility and decreased penetration of the zona pellucida. The findings indicate that the oocyte activation pathways triggered by ethanol/Sr2+ and sperm are distinguishable by CQ, and that CQ can be used as a selective inhibitor of oocyte activation induced by Sr2+ or ethanol treatment.